A case of sporadic Creutzfeldt-Jakob disease - Raoul Pop; Arta Teodorescu; Maria Tanasie; Ruxandra Joikits; Roxana Gheoca; Mihaela Simu (Romanian Journal of Neurology, 2012)
Sporadic Creutzfeldt-Jakob disease (CJD) is a very rare and fatal disease caused by prions – proteins with unique characteristics and infective potential. The typical clinical presentation is of a rapidly progressive dementia with myoclonus, cerebellar, pyramidal, extra pyramidal and visual signs. The definitive diagnosis is histological, but in the context of suggestive symptoms, EEG, MRI and 14-3-3 protein in the CSF can be very helpful. We present the case of a 47 year old female patient with rapid onset cognitive decline and myoclonus of the right arm, along with typical paraclinical findings.